2022
DOI: 10.1055/s-0041-1736514
|View full text |Cite
|
Sign up to set email alerts
|

Resultado funcional do procedimento de tenodese extra-articular lateral (TEL) como complemento à reconstrução do ligamento cruzado anterior: Uma metanálise

Abstract: Resumo Objetivos O objetivo deste estudo é revisar e analisar sistematicamente o desfecho funcional do procedimento de tenodese extra-articular lateral (TEL) em complemento à reconstrução do ligamento cruzado anterior (RLCA) em de estudos com alto nível de evidências. Métodos Realizamos a pesquisa bibliográfica para estudos clínicos comparando o método TEL como complemento à RCLA com a RLCA isolada. Os resultados principais foram a pontuação no Comitê Internacional de Documentação de Joelho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Because injury to structures in the anterolateral corner (ALC) of the knee is reported to result in a decrease in rotational stability [ 15 ], an increasing interest in several extra-articular surgical procedures to stabilize the ALC has been seen in the past years [ 1 , 4 ], and it has been reported that residual rotational laxity after ACLR decreased when this was combined with ALC reconstruction [ 2 , 7 , 13 ]. Moreover, reduced failure rate, increased subjective outcome scores, anterior tibial translation, and tibial internal rotation have been reported after ACLR combined with ALC reconstruction [ 2 , 3 , 12 , 16 , 17 ]. Indicators for this procedure seem to be young age (which might be a proxy for activity level [ 24 ]), participation in pivoting sports, and chronic ACL injury [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because injury to structures in the anterolateral corner (ALC) of the knee is reported to result in a decrease in rotational stability [ 15 ], an increasing interest in several extra-articular surgical procedures to stabilize the ALC has been seen in the past years [ 1 , 4 ], and it has been reported that residual rotational laxity after ACLR decreased when this was combined with ALC reconstruction [ 2 , 7 , 13 ]. Moreover, reduced failure rate, increased subjective outcome scores, anterior tibial translation, and tibial internal rotation have been reported after ACLR combined with ALC reconstruction [ 2 , 3 , 12 , 16 , 17 ]. Indicators for this procedure seem to be young age (which might be a proxy for activity level [ 24 ]), participation in pivoting sports, and chronic ACL injury [ 18 ].…”
Section: Introductionmentioning
confidence: 99%